Phylo-evo-devo: combining phylogenetics with evolutionary developmental biology - Minelli Alessandro (BMC Biology, 2009)
Abstract As a result of the integration of molecular and morphological approaches for the reconstruction of phylogenies, and of the intertwining of developmental and evolutionary biology, further prospects are open for a fruitful interaction between these two fields in what we may call a phylo-evo-devo approach. Wiegmann et al.'s molecular phylogeny of the holometabolous insect orders, recently published in BMC Biology, offers a good opportunity to revisit the inverted positions of wings and halteres in the Diptera and the Strepsiptera in terms of a putative homeotic mutation in the Hox gene Ultrabithorax. The main finding of this paper is that Strepsiptera are closely related to the Coleoptera rather than Diptera, as recently claimed. Through this exemplary case, the paper demonstrates the value of the reciprocal illumination we can expect from the integration of a good phylogeny and a sound knowledge of the evolvability of developmental mechanisms.